2015
DOI: 10.1140/epjp/i2015-15208-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spinor fields in Bianchi type-VI0 spacetime

Abstract: Within the scope of Bianchi type-VI cosmological model we study the role of spinor field in the evolution of the Universe. It is found that due to the spinor affine connections the energy-momentum tensor of the spinor field possesses non-diagonal components. The non-triviality of non-diagonal components of the energy-momentum tensor imposes some severe restrictions either on the spinor field or on the metric functions or on both of them. But unlike in cases of Bianchi type-I or V I 0 , in case of Bianchi type-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Within the scope of Bianchi type-III spacetime we study the role of spinor field on the evolution of the Universe. Unlike Bianchi type I, V or V I 0 cases where either both spinor mass and spinor field nonlinearity vanish [47][48][49] or the metric functions are similar to each other, i.e., a 1 ∼ a 2 ∼ a 3 in this case no such problem occurs. As one can see from (2.41) the spacetime remains locally rotationally symmetric and anisotropic all the time, though the isotropy of the spacetime can be achieved for a large proportionality constant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Within the scope of Bianchi type-III spacetime we study the role of spinor field on the evolution of the Universe. Unlike Bianchi type I, V or V I 0 cases where either both spinor mass and spinor field nonlinearity vanish [47][48][49] or the metric functions are similar to each other, i.e., a 1 ∼ a 2 ∼ a 3 in this case no such problem occurs. As one can see from (2.41) the spacetime remains locally rotationally symmetric and anisotropic all the time, though the isotropy of the spacetime can be achieved for a large proportionality constant.…”
Section: Discussionmentioning
confidence: 93%
“…In [47,48] it was shown that depending on the type restriction imposed on the non-diagonal components of the energy-momentum tensor, the initially Bianchi type-I evolve into a LRS Bianchi type-I spacetime or FRW one from the very beginning, whereas the model may describe a general Bianchi type-I spacetime but in that case the spinor field becomes massless and linear. The same thing happens for a Bianchi type-V I 0 spacetime, i.e., the geometry of Bianchi type-V I 0 spacetime does not allow the existence of a massive and nonlinear spinor field in some particular cases [49]. In this paper we study the role of spinor field on the evolution of a Bianchi type-III spacetime.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the ansatz (10) describes two Dirac fields, and for each of them, the energy-momentum tensor is not spherically symmetric, but their sum yields a spherically symmetric energy-momentum tensor. Now, substituting the ansatz (10) [by multiplying each row of (10) by the matrix (11)] and the metric (9) into the field equations ( 3) and (4), we have…”
Section: Formulating the Problem And General Equationsmentioning
confidence: 99%
“…[9] (wormhole solutions) and also in a cosmological context in Refs. [10][11][12][13][14], where the role of spinor fields in the evolution of anisotropic universes described by the Bianchi type I, III, V, VI, and VI 0 models or of an isotropic Friedmann-Robertson-Walker universe is studied. In turn, for spherically symmetric systems, localized regular solutions have been found in Refs.…”
Section: Introductionmentioning
confidence: 99%